Penggunaan Metode Permainan Tepuk Identitas Negara Untuk Meningkatkan Minat Mengenal Identitas Negara Indonesia Pada Anak Kelompok B TK Negeri Pembina Dharma Wanita: Using the National Identity Clapping Game Method to Increase Interest in Knowing Indonesian National Identity in Group B Children of the State Kindergarten of Pembina Dharma Wanita - Husnul Khatimah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to determine the use of the State Identity Tapping game method to increase interest in knowing Indonesian National Identity in Group B children at TK Negeri Pembina Dharma Wanita Bangkuang, Karau Kuala District, Academic Year 2020/2021 as many as 20 children. Learning improvement is carried out in 2 (cycles) carried out from October 19 2020 to October 30 2020. The instrument used was an observation sheet on teacher performance which was observed by colleagues, namely Ms. Indah Puspa Dewi from the beginning to the end of the learning process for each stage of improvement. Cycle I stage for 5 (five) consecutive days, from 19 October 2020 to 23 October 2020 and cycle II stage for 5 (five) consecutive days, from 26 October 2020 to 30 October 2020).